APA Handbook of Behavior Analysis, Vol. 1: Methods and Principles. 2013
DOI: 10.1037/13937-004
|View full text |Cite
|
Sign up to set email alerts
|

Applied behavior analysis.

Abstract: Applied behavior analysis (ABA) differs from other areas of applied psychology in many respects, but two are especially prominent. First, ABA is not an eclectic enterprise, borrowing theory and method from varied persuasions; it is grounded in the theoretical and experimental orientation of behavior analysis. Second, whereas most applied fields are distinguished by their emphasis on a particular clientele, problem, or setting, ABA is constrained only by its principles and methods. ABA focuses on any aspect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 194 publications
(225 reference statements)
0
10
0
2
Order By: Relevance
“…Despite an overall lack of effect of CBD on extinction training, results show a decrease in cocaine seeking behavior after one CBD (20 mg/kg) injection, in the first extinction day. In this session, experimental subjects typically show an 'extinction burst' in which operant responses are greatly increased in respect to the last session when cocaine was still available (Lerman et al, 2012;Skinner, 1938). Such 'extinction bursting' behavior is often considered as a measure of the urge to consume the drug (craving) that is not 18 affected by the acute pharmacological effects of the drug or the development of a previous extinction learning and thus, is viewed as a predictor of relapse behavior (Wee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite an overall lack of effect of CBD on extinction training, results show a decrease in cocaine seeking behavior after one CBD (20 mg/kg) injection, in the first extinction day. In this session, experimental subjects typically show an 'extinction burst' in which operant responses are greatly increased in respect to the last session when cocaine was still available (Lerman et al, 2012;Skinner, 1938). Such 'extinction bursting' behavior is often considered as a measure of the urge to consume the drug (craving) that is not 18 affected by the acute pharmacological effects of the drug or the development of a previous extinction learning and thus, is viewed as a predictor of relapse behavior (Wee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We found that both, Bonferroni; p < 0.01) ( Figure 1d). 'Extinction bursting' behavior is considered as the paradoxical increase of operant responding when the instrumental behavior is no longer followed by the reinforcer presentation (Lerman et al, 2012;Skinner, 1938). To characterize this feature, we calculated a two-way repeated measures ANOVA for nosepoke responding during the FR1 phase, the first extinction session and the last extinction day.…”
Section: Cbd Treatment Effects On the Extinction Of Cocaine Seeking Omentioning
confidence: 99%
“…Moreover, in light of recent events (i.e., the Covid-19 pandemic), perhaps researchers can evaluate variables influencing response persistence of behaviors related to public health behaviors such as mask wearing. After all, behavior analysis is only restricted by its principles and methods (Lerman, Iwata, & Hanley, 2013).…”
Section: Limitationsmentioning
confidence: 99%
“…Applied behavior analysts have taken this information and developed numerous techniques and treatment approaches for analyzing and changing behavior to improve lives. Because this approach is largely based on behavior and its consequences, the techniques generally involve teaching individuals more effective ways of behaving and making changes to the social consequences of existing behavior (Lerman, Iwata, & Hanley, 2013). ABA has been empirically shown to be effective in a wide variety of areas of concern, including parent training (Franks et al, 2013), substance abuse treatment (Silverman et al, 2007), dementia management (LeBlanc, Raetz, & Feliciano, 2011), brain injury rehabilitation (Heinicke & Carr, 2014), and occupational safety intervention (Geller, 2005), among others.…”
Section: Abamentioning
confidence: 99%